The power of failure : 27 ways to turn life's setbacks into success - Manz, Charles C. (Berrett-Koehler, 2002)
The Power of Failure offers both inspiration and advice on how failure can provide us with the foundation for long-term success. This book is loaded with inspiring real-life examples and stories, and filled with practical strategies that you can put to use immediately to fulfill your dreams.